Analisis partisipasi politik pemilih pemula pada pilkada serentak tahun 2020 di kecamatan sekernan - Mayestika, Tiwi; Anderson, Irzal; Sariani, Dona (Citizenship Education, Faculty of Education, Jambi University, 2022)
Community Participation Being an important thing in the life of the state, the fact in today's society is that participation is limited to the use of voting rights. but even then it is not good, from the results of the vote count carried out by the Muaro Jambi KPU in the 2020 Regional Head Election, it did not reach the KPU's target of 77.5%. The purpose of this study was to determine the form of political participation and the factors that influence the participation of novice voters in the implementation of the simultaneous regional elections in 2020. The informants of this study were the Chairperson of the KPU, the Head of the Technical Sub-section for Election Administration, Participation and Public Relations, and novice voters. is a qualitative research method. Data collection techniques in research are interviews, and documentation. The data analysis technique of this research is descriptive qualitative. The results showed that the forms of political participation were analyzed through the theory of political participation by rush and althoff which divided participation into 10 forms, in research on novice voters only optimal in several forms and factors that influence novice voters in participating include the stimuli received, social characteristics, characteristics personal, political situation and environment and political education. Seeing the importance of the purpose of participation in the life of the state, it is a must for the government, KPU, community and beginner voters themselves to play an active role in building a good habit for novice voters through preventive measures by socializing, counseling and building a conducive political environment for novice voters. in order to be comfortable to participate.